(untitled) (Research, Society and Development, 2022)
The state of Tocantins has an indigenous population of approximately 13 thousand people whose way of life has been progressively affected due to economic and cultural colonization. Over the years after the 1988 Constitution, several policy projects for indigenous health were published, however this population still suffers from social exclusion and low access to health care services. This paper proposes an analysis of the main diseases related to hospitalization and mortality rates among indigenous peoples of Tocantins, in order to contribute to the identification of the epidemiological profile of indigenous peoples in the state. Therefore, a statistical, longitudinal, retrospective, case-control study was carried out, through the collection of public data on morbidity and mortality indicators of the indigenous population in Tocantins between the years 2011 and 2019. Analysis of the profile data epidemiological study of indigenous health in Tocantins showed that preventable diseases related to infection and the respiratory system occupy a considerable margin of morbidity, with no considerable incidence of non-communicable chronic diseases such as hypertension and diabetes mellitus among this vulnerable group in the population.